2013
DOI: 10.1128/aac.01632-12
|View full text |Cite
|
Sign up to set email alerts
|

Increased Survival of Antibiotic-Resistant Escherichia coli inside Macrophages

Abstract: Mutations causing antibiotic resistance usually incur a fitness cost in the absence of antibiotics. The magnitude of such costs is known to vary with the environment. Little is known about the fitness effects of antibiotic resistance mutations when bacteria confront the host's immune system. Here, we study the fitness effects of mutations in the rpoB, rpsL, and gyrA genes, which confer resistance to rifampin, streptomycin, and nalidixic acid, respectively. These antibiotics are frequently used in the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 53 publications
2
45
0
2
Order By: Relevance
“…The relative fitness of susceptible and resistant bacteria is measured by their reproductive success during in vitro culture. Many studies have reported that resistance commonly creates a fitness burden (51, 52); however, resistant mutants with no measurable costs or those with a slight advantage over the wild type have also been observed (53,54), which is in agreement with our observations. However, in the presence of 10 g ml Ϫ1 CHX, the biomass of the WT15 biofilms increased over a 24-h period, whereas there was an apparent cessation of biofilm development in the CHX-treated MT51 biofilms compared to that in their untreated counterparts.…”
Section: Discussionsupporting
confidence: 83%
“…The relative fitness of susceptible and resistant bacteria is measured by their reproductive success during in vitro culture. Many studies have reported that resistance commonly creates a fitness burden (51, 52); however, resistant mutants with no measurable costs or those with a slight advantage over the wild type have also been observed (53,54), which is in agreement with our observations. However, in the presence of 10 g ml Ϫ1 CHX, the biomass of the WT15 biofilms increased over a 24-h period, whereas there was an apparent cessation of biofilm development in the CHX-treated MT51 biofilms compared to that in their untreated counterparts.…”
Section: Discussionsupporting
confidence: 83%
“…Many of these pathogens persist inside the cells of the immune system. Miskinyte and Gordo (Miskinyte and Gordo 2013) examined how a commensal E. coli was able to develop the virulence needed to persist inside macrophages of the immune system. Working in mice, they found that when maintained in vitro under the selective pressure of host macrophages, commensal E. coli can evolve virulent clones that escape phagocytosis and macrophage killing in vitro , while increasing their pathogenicity in vivo .…”
Section: Commensal Bacteria At the Crossroad Between Inflammation Andmentioning
confidence: 99%
“…We consider values of the mutant's growth rate larger or larger or smaller than r = 2 (that of the wild type) motivated by the attention that the fitness effect of resistance has received over the past decade (Andersson and Hughes 2010;Melnyk et al 2015). While resistance mutations typically impair growth to a certain extent (Schrag et al 1997;Reynolds 2000), some can be advantageous even in the absence of the drug (Luo et al 2005;Marcusson et al 2009;Vickers et al 2009;Baker et al 2013;Miskinyte and Gordo 2013;Rodríguez-Verdugo et al 2013). In addition, there is a growing concern regarding the selection for resistance under the nonlethal antibiotic concentrations commonly found in many clinical and natural environments (Gullberg et al 2011;Andersson and Hughes 2014;Larsson 2014;Johnning et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Such conditions are not rare in clinical and agricultural settings, where antibiotic gradients occur naturally in wastewater or inside human and animal body compartments (Baquero and Negri 1997;Kümmerer 2004). In addition, recent reports showed that some resistance mutations can be advantageous in the absence of antibiotics (Luo et al 2005;Marcusson et al 2009;Vickers et al 2009;Baker et al 2013;Miskinyte and Gordo 2013;Rodríguez-Verdugo et al 2013). Interestingly, some of these benefits were described to arise as a by-product of adaptation to common circumstances, such as thermal stress (Rodríguez-Verdugo et al 2013), macrophage phagocytosis (Miskinyte and Gordo 2013), or growth impairment caused by previously acquired resistance mutations (Marcusson et al 2009).…”
Section: Discussionmentioning
confidence: 99%